Knowledge Creation and its Impact on Task Performance - Bernik, Nejc; Šprajc, Polona (45th International Conference on Organizational Science Development: Organization and the Longevity Society, Conference Proceedings, 2026)
The paper examines knowledge creation in public organisations and explores its relationship with task performance as well as employee education and training. Based on a survey conducted among Slovenian public servants, the relationships between the selected variables were analysed using correlation analysis. The results indicate a statistically significant positive relationship between task performance and knowledge creation, confirming the importance of effective task execution for the development of new knowledge in the public sector. In contrast, the relationship between education, training, and knowledge creation is not statistically significant. The findings indicate that task performance is an important factor in the development of knowledge in public organisations., providing a basis for further research in this field.